Mr. Texas [large type] - Wright, Lawrence, 1947- (Random House Large Print, 2023)
"Sonny Lamb is an affable, if floundering, rancher with the unfortunate habit of becoming a punchline in his Texas hometown. Most recently, he bought his own bull at auction, saving it from being sold to a slaughterhouse. But when a fire breaks out at a neighbors farm, Sonny makes headlines in another way: Not waiting for help, he bolts to the farm and heroically saves the familys daughter and her horse, riding the animal out of their burning barn. Within days of the event, he attracts the notice of a mysterious man named L.D. who arrives at his door and asks if he'd like to run as a Republican for his districts representative seat. Though Sonny has zero experience and doesnt consider himself political in the least, he decides to throw his hat in the ring . . . and he wins. As Sonny navigates life in politics, from running a campaign to negotiating in the capitol, he must learn the ropes, weighing his own ethics and environmental concerns against the pressures of veteran politicians, savvy lobbyists, and his own party. In tracing Sonny's attempt to balance his marriage and morality with an increasingly volatile professional life, Lawrence Wright has crafted a hilarious, immensely clever rollercoaster ride about one man's pursuit of goodness in the Lonestar State"--